The INOVASI PRODUK MINUMAN TEH CASCARA DARI LIMBAH KULIT KOPI SEBAGAI SOLUSI PENGURANGAN LIMBAH PERTANIAN OLEH TEACHING FACTORY PENGOLAHAN PRODUK KOPI - Rosdiana, Eva; Nugroho, Setyo Andi Nugroho; Pujiastuti, Pujiastuti; Nirmala Kusumaningtyas, Rizky; Santika, Putri; Cinantya Anindita, Devina (Politeknik Negeri Jember, 2024)
Coffee production from 2020 to 2022 experienced fluctuations. In 2020, coffee production reached 762.38 thousand tons, increasing to 786.19 thousand tons in 2021, or a 3.12% rise. As coffee production increases, the amount of waste produced also rises. Coffee husks make up 48% of physical composition, consisting of 42% fruit skin and 6% bean skin. The proportion of coffee husk generated during processing is quite significant, ranging from 40-45%. Coffee husks contain 10.4% crude protein and 17.2% crude fiber. Coffee husks also contain phenolic compounds with antimicrobial and antioxidant properties. Coffee husk extract can inhibit hyaluronidase, presenting potential to reduce allergies and inflammation. Given its composition and benefits, our service team has developed a cascara tea product. The active compounds in cascara include 1.8-8.56% tannins, 6.5% pectin, 1.3% caffeine, 2.6% chlorogenic acid, 1.6% caffeic acid, and 43% total anthocyanins. The community service program was conducted from June to November 2024. The target audience for the program was the Teaching Factory for Coffee Product Processing. The results showed that knowledge among technicians and students in the pre-test phase was highest (40%) in recognizing coffee waste, environmental impact, and health benefits of cascara tea, while the lowest (30%) was in cascara tea production. Post-test results showed a 100% improvement in cascara tea production skills. These results indicate that more than 70% of technicians and students understood and were able to produce cascara tea